Detection of Anti-SARS-CoV-2 Nucleocapsid and Spike Antibodies in Patients with Coronavirus Disease 2019 in Japan. Issue 16 (April 2022) - Furukawa, Hiroshi; Oka, Shomi; Higuchi, Takashi; Yamaguchi, Miho; Uchiyama, Shota; Koiwa, Tomohiro; Nakama, Moriyuki; Minegishi, Masaaki; Nagai, Hideaki; Tohma, Shigeto
OBJECTIVES: Coronavirus Disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Serological testing for anti-SARS-CoV-2 nucleocapsid (N) antibodies (Abs) and anti-SARS-CoV-2 spike (S) Abs is performed to detect prior COVID-19 infection. It is still controversial which antibodies are the most sensitive and specific, and which can be detected earliest after infection. Here, we evaluated the results of serological tests of anti-SARS-CoV-2 N and S Abs in Japan. METHODS: Symptomatic COVID-19 patients (n = 84) and control patients with rheumatoid arthritis (n = 93) were recruited at Tokyo National Hospital. Anti-SARS-CoV-2 N and S Abs were measured by commercial electrochemiluminescence immunoassays. RESULTS: The fraction of patients positive for anti-SARS-CoV-2 N and S Abs was highest >14 days after symptom onset. The frequency of anti-SARS-CoV-2 S Ab positivity at this time (80.4%) tended to be slightly but not significantly lower than anti-SARS-CoV-2 N Ab positivity (84.8%). Optimized cut-off levels for anti-SARS-CoV-2 N and S Ab positivity were lower than the manufacturer's recommended cut-off levels. Using multiple linear regression analyzes with anti-SARS-CoV-2 N and S Abs, we created an Ab-index with high sensitivity. CONCLUSION: To increase the sensitivity of serological diagnostic tests for COVID-19, it is suggested that both anti-SARS-CoV-2 N and S Abs should be measured and cut-off levels decreased.